AGRICULTURAL PERFORMANCE OF SWEET CASSAVA CULTIVARS IN CERRADO ENVIRONMENT - Paz, Rogério Borges de Oliveira (2020)
Sweet cassava is cultivated throughout the Brazilian territory, but it needs to be better studied in the Cerrado region that has potential for its cultivation. The objective of this work was to evaluate the behavior of sweet cassava cultivars in Cerrado soil for two harvests. The experiment was carried out in the cultivars of 2016-2017 and 2017-2018 in Jataí-GO, with six cultivars (BRS-397, BRS-398, BRS-399, BRS-400, BRS-401 and IAC-576/70). A randomized complete block design was used with three replications in a factorial scheme, being the cultivar factors and harvests. The number of stems, stem diameter, height of the first branch, height of plants, number of roots per plant, root length, root diameter, fresh root mass, fresh shoot mass, harvest index and time of cooking. All data were submitted to analysis of variance, and the means were grouped by the Scott-Knott method. There was interaction between the sources of variation for fresh root mass and fresh shoot mass. The cultivar BRS-399 obtained better root productivity in the two harvests. The cultivars BRS-399, BRS-400, BRS-401 and IAC-576/70 increased the fresh mass of the aerial part from the first to the second crop. The harvest index of cultivars BRS 400 and BRS 401 decreased from the first to the second year of cultivation. It was concluded that under the conditions of each harvest sweet cassava cultivars presented high root yield. The BRS 399 showed stable agronomic behavior in the experimental crops with higher root productivity.